2015
DOI: 10.4081/aiua.2015.3.198
|View full text |Cite
|
Sign up to set email alerts
|

The histology and the proapoptotic control in the ipsilateral and the contralateral testes following unilateral vasectomy

Abstract: The procedure causes destruction in the testicular structure by causing bilateral intratubular germ cell necrosis, unilateral obstruction, increase in the tubular pressure and processes that are aggravated by some probable autoimmune reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…As expected, the remarks made in the case of human patients apply to rodents as well. Seminal obstruction, regardless of the testes and side, reduces the rate of spermatogenesis, concluding that unilateral vasectomy induces vast histological changes that cover unilateral obstruction, intratubular germ cell necrosis, and an increase in tubular pressure probably linked to autoimmune responses [ 176 ].…”
Section: Resultsmentioning
confidence: 99%
“…As expected, the remarks made in the case of human patients apply to rodents as well. Seminal obstruction, regardless of the testes and side, reduces the rate of spermatogenesis, concluding that unilateral vasectomy induces vast histological changes that cover unilateral obstruction, intratubular germ cell necrosis, and an increase in tubular pressure probably linked to autoimmune responses [ 176 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that seminal obstruction on one side might reduce the rate of spermatogenesis, thus indicating that unilateral vasectomy is not an ideal modality for the treatment of epididymitis with PUCs [15]. Once PUCs have been excised, anatomical reconstruction of the seminal passage appears to be a far superior option than other techniques.…”
Section: Resultsmentioning
confidence: 99%